Outcome in octogenarian patients with lower extremity artery disease after endovascular revascularisation: a retrospective single-centre cohort study using in-patient data. Issue 8 (1st August 2022) - Lakomek, Antonia; Köppe, Jeanette; Barenbrock, Henrike; Volkery, Kristina; Feld, Jannik; Makowski, Lena; Engelbertz, Christiane; Reinecke, Holger; Malyar, Nasser M; Freisinger, Eva
Abstract : Objectives: To investigate the clinical benefit of endovascular revascularisation (EVR) in octogenarian (aged ≥80 years) patients with lower extremity artery disease (LEAD). Design: Retrospective single-centre study. Setting: University hospital with a specialised centre for vascular medicine. Participants: 681 LEAD patients undergoing EVR between 2010 and 2016 were stratified by age. Main outcome measure: Technical success, complications and mortality. Results: The cohort comprised 172 (25.3%) octogenarian and 509 (74.7%) non-octogenarian patients. Despite higher LEAD stages and complexity of EVR in octogenarians, primary technical success rate (79% octogenarians vs 86% non-octogenarians, p=0.006) and 1-year survival (87% vs 96%, p<0.001) were overall on high levels. Especially for the octogenarians, 1-year survival depends on the presence of chronic limb-threatening ischaemia (CLTI) (octogenarians: non-CLTI 98%; CLTI 79% p<0.001 vs non-octogenarians: non-CLTI 99%; CLTI 91%, p<0.001). In octogenarians, female sex (HR 0.45; 95% CI (0.24 to 0.86); p=0.015), the intake of statins (HR 0.34; 95% CI 0.19 to 0.65; p=0.001) and platelet aggregation inhibitors (HR 0.10; 95% CI 0.02 to 0.45; p=0.003) were independently associated with improved survival after EVR. Conclusion: EVR can be performed safely and with sustained clinical benefit also in octogenarian patients with LEAD. After-care including medical adherence is of particular importance to improve long-term survival.